Mapping Over-indebtedness of Microfinance Clients in Indonesia and Tanzania: The Importance of Analysing Microfinance beyond its Outreach and Sustainability - Kurniawan Saefullah; Irvan Sadikin; J.C.M. de Bekker; Musuto Mutaragara Chirangi (Budapest International Research and Critics University, 2022)
This paper attempts to describe the importance of mapping the over-indebtedness of microfinance clients. While most research into the field of microfinance confirms its role in alleviating poverty through its outreach, little research has been done to evaluate its sustainability. More so, the analysis of microfinance clients regarding their over-indebtedness is still limited, although it could assist microfinance institutions (MFI’s) in acquiring specific information concerning the profile of their clients. Using a qualitative approach, through a literature study of recent evaluations of microfinance lending schemes, in combination with primary data collected by the authors with the context of global south-south dialogue between Indonesia and Tanzania, this paper highlights the importance of mapping microfinance clients regarding their condition of over-indebtedness. It also suggests policy makers to anticipate the causes of over-indebtedness of clients in designing and applying policies to avoid the failure of microfinance in alleviating poverty and sustain its support of micro- or small-scale enterprises.